Importancia económica y perspectivas de la ampliación del Canal de Panamá (2014)
The aim of this paper is to present the importance of the Panama Canal to the U.S. economy and the main effects that bring the extension thereof. The technology provided by the Canal has increased the value of the geographical position of the Isthmus as a transportation hub for international maritime trade. Economic diversification generates growth related to transportation, services, communications, trade and other complementary transit through the waterway activities. The canal expansion will increase the Canal's capacity to serve the growing demand for cargo and maritime trade route, but can lead to excessive dependence on Canal in Panamanian economy.